American Older Adults in the Time of COVID-19: Vulnerability Types, Aging Attitudes, and Emotional Responses - Mingqi Fu; Jing Guo; Xi Chen; Boxun Han; Farooq Ahmed; Muhammad Shahid; Qilin Zhang (Institute of Labor Economics (IZA), 2022)
With 1582 respondents from the Health and Retirement Survey (HRS), this study investigates the heterogeneity in older adults' vulnerability and examines the relationship between vulnerability types, aging attitudes and emotional responses. International Positive and Negative Affect Schedule Short-form (I-PANAS-SF) and Attitudes toward own aging (ATOT) were used to assess the emotional experiences and aging attitudes, and 14 types of pandemic-related deprivations evaluated individuals' vulnerability. Latent class analysis was used to explore the vulnerability types, and weighted linear regressions examined the relationship between vulnerability, aging attitudes and emotional responses. Results showed that the proportion for individuals with mild vulnerability (MV), health care use vulnerability (HV), and dual vulnerability in health care use and finances (DVs) was 67%, 22%, and 11%, respectively. Older adults aged below 65, Hispanics and non-Hispanic Blacks, and those not eligible for Medicaid were more likely to have HV or DVS. The relationship between vulnerability and positive emotions was insignificant, yet individuals with HV (beta=0.10, SE=0.16) or DVs (beta=0.09, SE=0.28) were likely to have more negative emotions than their mildly vulnerable counterparts. Furthermore, aging attitudes moderated the relationship between vulnerability and emotions. Encouraging positive aging attitudes might be helpful for older adults to have better emotional well-being, especially for those with DVs.
Keywords: J14; D91; I14; 330; emotion; aging attitudes; vulnerability; older adults; COVID-19